Characterization of solid waste in the Capanique Campus of the Private University of Tacna - Lazo Ramos, Richard Sabino (2020)
The purpose of the study was to study the characteristics and know the amount of solid waste generated by the university community in the Capanique campus of the Private University of Tacna (UPT). For this study, the municipal solid waste regulations of the MINAM (2012) were applied. The obtaining of the sample was applying the method of the cuarteo which allowed to know the characteristics of the recyclable and organic material that was of a 59,0 % of the total of solid residues, inside them the PET (plastic bottles) with the 14, 52% and organic matter with 10,93 %. Regarding the amount of waste generated, the volumetric weight or density "in situ" was determined, which was 102.3 kg / m³, which indicates a low density of residues in the deposits of the University. Likewise, the generation rate was estimated. per capita that was 0.5 (kg / day / person). According to the waste generation group it was shown that the largest amount of waste was generated in the administrative area and by full-time teachers 0.11 (kg / day / person), in addition the campus that generated the most waste was the campus 3 constituted by the Faculty of Business Sciences with 190,932 kg / week and the generation of hospital waste from the University Clinic of the Faculty of Health Sciences was 1 235 kg / day. The present investigation means a contribution for an adequate management of solid waste in the Private University of Tacna